ANALYZING VOCABULARY LEVEL OF THE STUDENTS’ ESSAY WRITING AND ACADEMIC TEXTBOOK UTILIZING LEXTUTOR - Nur Aliyah Nur (ETERNAL (English, Teaching, Learning and Research Journal), 2015)
The objectives of this study were to describe the result of the vocabulary level analysis of the students‟ essay writing and academic textbook utilizing lextutor, to investigate the effects of introducing VP web tool (lextutor) on students‟ vocabulary level in writing academic essays at the English Education Department of UIN Alauddin Makassar academic year 2011/2012, to correlate the vocabulary level of their essay writing and their academic textbook, and to investigate their opinion on lextutor as a VP web tool analyzer towards their essay writing. The data were collected through the VP web tool and interview using four different academic essays of 100 students involved. The data analysis and interpretation indicated: (1) the vocabulary levels of the students‟ essay writings were smaller than the standard percentage of VP web tool exclude their K1; (2) the changes of vocabulary profile of the students‟ academic essays were not significantly affected by the introducing of VP web tool as the trendlines did not show the normal pattern of time-series graphic line design; (3) findings on vocabulary profile of the students‟ academic reading text showed similar patterns of graphic trendline to those in the academic essays; (4) the use of K2 and AWL in the students‟ academic essays were proved to be significantly different before and after the intervention but not significant in K1 and OL vocabulary profile; (5) there is not any significant correlation between the vocabulary profile of academic reading texts and vocabulary profile of students‟ essay writing in academic word list; and (6) the VP web tool is good and gives a lot of benefit to students to assess their vocabulary level when dealing with academic essay writing, and they have awareness of using more and appropriate academic vocabulary in writing academic tasks. The findings led to the recommendation of an extensive use of VP web tool to analyze vocabulary level used by students in their academic essays.